Boundary layer flow on permeable flat surface in Ag-Al2O3/Water hybrid nanofluid with viscous dissipation - Muhammad Khairul Anuar, Mohamed; Hussanan, Abid; Alkasasbeh, Hamzeh Taha; Widodo, Basuki; Mohd Zuki, Salleh (Penerbit UMP, 2021)
Seeking the better performance nanofluid but with low cost of production, presence challenged. Metal nanomaterial is good in both thermal and electric conductivity but expensive while oxide nanomaterial does oppositely. The present study solved numerically the laminar boundary layer flow over a permeable flat surface in a blended metal-oxide hybrid nanofluid plate with viscous dissipation effects. The similarity equations in the form of the set of ordinary differential equations are reduced from the non-linear partial differential equations before being solved numerically using the Runge-Kutta-Fehlberg method in MAPLE. The numerical solution is obtained for the reduced skin friction coefficient and reduced Nusselt number as well as the temperature and velocity profiles. The flow features and the heat transfer characteristic for the Eckert number, permeability parameter and nanoparticle volume fraction are analyzed and discussed. The AgAl2O3 water-based hybrid nanofluid tested in this study shows competitive results with the Ag waterbased nanofluid in certain cases